Roman theatres : an architectural study - Sear, Frank (Oxford ; New York : Oxford University Press, 2006)
This book is an up-to-date and comprehensive account of Roman theatre architecture. It contains information, plans, and photographs of every theatre in the Roman Empire for which there is archaeological evidence, together with a full analysis of how Roman theatres were designed, built, and paid for, and how theatres differ in different parts of the Roman Empire. It is lavishly illustrated with plans, text figures, photographs, and maps. - ;This book is a definitive architectural study of Roman theatre architecture. In nine chapters it brings together a massive amount of archaeological, literar.
Contents; List of Tables; List of Plans; List of Figures; List of Plates; List of Maps; Abbreviations; 1. Theatre and Audience; 2. Finance and Building; 3. Roman Theatre Design; 4. Theatres and Related Buildings; 5. Republican Theatres in Italy; 6. The Theatres of Rome; 7. The Cavea and Orchestra; 8. The Scene Building; 9. Provincial Theatres; CATALOGUE; Bibliography; Index of Ancient Authors; Index of Inscriptions; Index of Place Names; General Index; Index of Persons and Peoples; Maps; Figures; Plates.
Includes bibliographical references (pages 425-431) and indexes.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
eBooks on EBSCOhost
Keywords: Theaters -- Rome; Archaeology -- Rome; Rome -- Antiquities -- Catalogs; Archéologie -- Rome; Rome -- Antiquités -- Catalogues; ARCHITECTURE -- Buildings -- Public, Commercial & Industrial; Antiquities; Archaeology; Theaters; Rome (Empire); Catalogs